Correction: A hybrid blue perovskite@metal–organic gel (MOG) nanocomposite: simultaneous improvement of luminescence and stability. Issue 11 (2nd March 2022) - Mollick, Samraj; Mandal, Tarak Nath; Jana, Atanu; Fajal, Sahel; Ghosh, Sujit K.
Abstract : Correction for 'A hybrid blue perovskite@metal–organic gel (MOG) nanocomposite: simultaneous improvement of luminescence and stability' by Samraj Mollick et al., Chem. Sci., 2019, 10, 10524–10530, DOI: ; 10.1039/C9SC03829A .